Rehabilitation Policy Against Narcotics Users As A Study Of Act Number 35 Of 2009 On Narcotics - Indah Rachmawati; Lathifah Hanim (Jurnal Daulat Hukum, 2019)
Writing is entitled "Rehabilitation Policy Against Narcotics Users As A Study Of Act Number 35 Of 2009 Concerning Narcotics". Based on the description in this thesis, that will be examined are: 1). How social rehabilitation program policies towards drug users that have been set by the Act Number 35 of 2009 on narcotics? 2). How social rehabilitation constraints against drug users and measures taken to address them? 3). How social rehabilitation program policies against drug users in the future from the study of Act Number 35 of 2009 on narcotics? The study concluded that: 1). Seeing the criminal provisions of Article 127 paragraph (2) and (3), it can be concluded that the judge in deciding the case mentioned in Article 127 paragraph (1) is obliged to pay attention to clauses governing the provision of rehabilitation so that later addicts and victims abusers of narcotics can The rehabilitation of both medical rehabilitation and social rehabilitation and no longer subject to imprisonment or imprisonment for rehabilitation is counted as time serving his sentence. 2). Constraints that come from this government by mentioning that there are five (5) constraints, namely: there is no stipulation of a special place for addicts and victims of abusers of narcotics for the rehabilitation, rehabilitation cost problem for convicted drug abuse, no rehab appointed by the Government, the differences between the testimony of the defendant, witnesses and Criminal laboratory results, there is a problem of execution. While the solution of the problems are: Need to immediately set a special place for addicts and victims of drug abuse for the rehabilitation, the Government should have the extra funds to finance all decisions rehabilitation for victims of substance abuse, the Government should have the scale of priority to the problem of rehabilitation, Investigator and the authorities in handling should be more careful in handling the problem of drug abuse and have proof of accurate, execution issue should be considered from the extent of the offense. 3). Law enforcement Law Number 35 of 2009 concerning Narcotics which is ideal must be accompanied by awareness that law enforcement as part of the legal subsystem, is also a social subsystem, so that the influence of the environment is quite influential on the principles of law enforcement and legal principles that apply in the national environment. civilized nationKeywords: Rehabilitation Policy, Narcotics, Rehabilitation.